Multi-element vertical array for zero-spacing interferometry - Sutinjo, Adrian; Ung, D.; Wayth, Randall; Hall, Peter (2016)
Measurement of integrated sky noise is desirable in radio astronomy for flux density calibration and cosmological signal detection. The ultimate goal is to make such measurement while adding negligible system noise. This is the challenge of zero-spacing interferometry. We discuss the theory of an interferometer that consists of a vertical array whose outputs are correlated, weighted, and then summed to realize the zero-spacing response. We describe a design equation based on array synthesis and provide a simple example that covers the 50-250 MHz frequency band.